Punch-Drunk Love - Anderson, Paul Thomas; Don Mc Manus, Andrews; David Schrempf; Emily Watson; Guzmán Jason; Hoffman Luis; Philip Seymour; Adam Sandler (USA Revolution Studios, 2002)
Barry Egan (Adam Sandler) is a small business owner with seven sisters whose abuse has kept him alone and unable to fall in love. When a harmonium and a mysterious woman (Emily Watson) enter his life, his romantic journey begins.
A beleaguered small-business owner gets a harmonium and embarks on a romantic journey with a mysterious woman.
Paul Thomas Anderson
Language: English Subtitles: English, Turkish, Arabic, Hindi
Keywords: Drama; Romance; Comedy